Anticonvulsant Action of GluN2A-Preferring Antagonist PEAQX in Developing Rats - Pavel Mares; Grygoriy Tsenov; Hana Kubova (MDPI AG, 2021)
The GluN2A subunit of N-methyl-D-aspartate (NMDA) receptors becomes dominant during postnatal development, overgrowing the originally dominant GluN2B subunit. The aim of our study was to show changes of anticonvulsant action of the GluN2A subunit-preferring antagonist during postnatal development of rats. Possible anticonvulsant action of GluN2A-preferring antagonist of NMDA receptors P = [[[(1S)-1-(4-bromophenyl)ethyl]amino](1,2,3,4-tetrahydro-2,3-dioxo-5-quinoxalinyl)methyl]phosphonic acid tetrasodium salt (PEAQX) (5, 10, 20 mg/kg s.c.) was tested in 12-, 18-, and 25-day-old rats in three models of convulsive seizures. Pentylenetetrazol-induced generalized seizures with a loss of righting reflexes generated in the brainstem were suppressed in all three age groups in a dose-dependent manner. Minimal clonic seizures with preserved righting ability exhibited only moderately prolonged latency after the highest dose of PEAQX. Anticonvulsant action of all three doses of PEAQX against cortical epileptic afterdischarges (generated in the forebrain) was found in the 25-day-old animals. The highest dose (20 mg/kg) was efficient also in the two younger groups, which might be due to lower specificity of PEAQX and its partial affinity to the GluN2B subunit. Our results are in agreement with the postero-anterior maturation gradient of subunit composition of NMDA receptors (i.e., an increase of GluN2A representation). In spite of the lower selectivity of PEAQX, our data demonstrate, for the first time, developmental differences in comparison with an antagonist of NMDA receptors with a dominant GluN2B subunit.